LITERATUR REVIEW : PENERAPAN TERAPI MUROTTAL AL-QUR’AN TERHADAP PENURUNAN INTENSITAS NYERIPADA KLIEN POST OPERASI - Sakiyan, Ahmad Muzaki, Amelia Khoirunnisa (AKPER Pemkab Purworejo, 2021)
Background: Surgery is the act of opening or showing body parts by cutting and closing them again by suturing the wound as an invasive treatment carried out by the medical team. Surgery is divided into two, namely Major Surgery and Minor Surgery. Surgery can cause discomfort or pain, one of the non-pharmacological techniques is murottal al-quran therapy. Objective: Knowing the application of listening therapy to the al-quran reading to reduce pain intensity in postoperative clients. Methods: This type of research is a literature review, namely a description of the theory, findings, and other research materials obtained from reference materials to be used as the basis for research activities to formulate a clear frame of mind from the formulation of the problem to be studied. Results: The researchers concluded based on these 5 journals that the murottal al-quran technique was effective in reducing pain levels in the postoperative period. Conclusion: Based on the five journals that have been presented, it is found that the murottal al-quran technique can reduce the level of pain intensity in postoperative clients.